Development and Preliminary Evaluation of a Food Literacy Measure for Use With Young People in Canada - Tracey Borland; Michael D.T. Fung; Emily Taylor; Michael Chaiton; Robert Schwartz; Heather Thomas; Elsie Azevedo Perry; H. Ruby Samra; Lucy Valleau; Sharon I. Kirkpatrick (Journal of the Academy of Nutrition and Dietetics, 2025)

Climate media amidst technopolitical change: challenges, transformations, and new directions for research - Rachel Wetts; Hanna E. Morris; Maxwell Boykoff; Brenda McNally; James Painter; Mary Sanford; Emily P. Diamond; Marc Esteve-del-Valle; Loredana Loy; Kelly E. Perry; Urooj S. Raja; Robin Tschötschel (Climatic Change, 2025)
In this essay, we seek to provide a meta-level view of research on mediated climate change communication, taking stock of its achievements, historical and contemporary challenges, and future directions. While existing climate media scholarship has generated important insights to guide research and practice, recent empirical developments and technopolitical transformations challenge the traditional structure of climate media research. Historically, this research developed a tripartite structure where scholars have tended to focus on one of three distinct phases of the mediated communication process: (1) the production of narratives, frames, images, and other forms of communication about climate change; (2) the content and dissemination of these communication artifacts by and across media industries and institutions; and (3) these artifacts’ reception by and effects on policymakers, partisans, and publics. However, recent developments in communication technologies, media ecosystems, and the broader political landscape—including the increasing importance of social media and AI, new forms of climate obstruction, and rising antidemocratic forces across borders—have made these traditional lines of demarcation increasingly unworkable. While the lines of demarcation between production, dissemination, and reception are increasingly blurred in important new empirical phenomena, each has remained central in many scholarly works and the development of research questions. This persistence of the tripartite model, we argue, has caused climate media research to be slow to reflect the shifting dynamics of mediated climate communication today. After describing and analyzing the structural challenges that make doing more comprehensive climate media research so challenging, we conclude with proposals for new directions for scholarship that can help future research more fully contend with recent technopolitical transformations and move towards actionable research that is capable of grappling with and motivating robust responses to the complexities of climate change amid mounting authoritarian threats.

Assessing greenspace and cardiovascular health through deep-learning analysis of street-view imagery in a cohort of US children - Li Yi; Sheryl Rifas-Shiman; Marcia Pescador Jimenez; Pi-I Debby Lin; Esra Suel; Perry Hystad; Andrew Larkin; Steve Hankey; Wenwen Zhang; Jochem Klompmaker; Emily Oken; Marie-France Hivert; et al. (Environmental Research, 2025)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Scoping the lines: Assessing the mountain biking research terrain and calling for a holistic scholarship agenda - Katelyn P. Kuklinski; Kimberly J. Coleman; Jessica E. Leahy; Elizabeth E. Perry; Emily Reinhardt; Luke Briccetti (Journal of Outdoor Recreation and Tourism, 2024)

Lymphomatosis as a Cause of Abdominal Pain and Distension in Two Adult Horses - Laura R. Perry; Amanda J. Butler; Emily John; Shannon Martinson; Melanie Buote; Kimberley Foote; Shelley Burton; William B. Stoughton (Journal of Equine Veterinary Science, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Physician perceptions of a multidisciplinary endocarditis team - Sami El-Dalati; Irina Khurana; Nathaniel Soper; Daniel Cronin; Michael Shea; Richard L. Weinberg; James Riddell; Laraine Washer; Emily Shuman; James Burke; Sadhana Murali; D. Alexander Perry; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

Genetic structure in the European endemic seabird, Phalacrocorax aristotelis , shaped by a complex interaction of historical and contemporary, physical and nonphysical drivers - Evanthia Thanou; Stefano Sponza; Emily J. Nelson; Annika Perry; Sarah Wanless; Francis Daunt; Stephen Cavers (Molecular Ecology, 2017)
Geographically separated populations tend to be less connected by gene flow, as a result of physical or nonphysical barriers preventing dispersal, and this can lead to genetic structure. In this context, highly mobile organisms such as seabirds are interesting because the small effect of physical barriers means nonphysical ones may be relatively more important. Here, we use microsatellite and mitochondrial data to explore the genetic structure and phylogeography of Atlantic and Mediterranean populations of a European endemic seabird, the European shag, Phalacrocorax aristotelis , and identify the primary drivers of their diversification. Analyses of mitochondrial markers revealed three phylogenetic lineages grouping the North Atlantic, Spanish/Corsican and eastern Mediterranean populations, apparently arising from fragmentation during the Pleistocene followed by range expansion. These traces of historical fragmentation were also evident in the genetic structure estimated by microsatellite markers, despite significant contemporary gene flow among adjacent populations. Stronger genetic structure, probably promoted by landscape, philopatry and local adaptation, was found among distant populations and those separated by physical and ecological barriers. This study highlights the enduring effect of Pleistocene climatic changes on shag populations, especially within the Mediterranean Basin, and suggests a role for cryptic northern refugia, as well as known southern refugia, on the genetic structure of European seabirds. Finally, it outlines how contemporary ecological barriers and behavioural traits may maintain population divergence, despite long‐distance dispersal triggered by extreme environmental conditions (e.g. population crashes).